Reshaping Organizations – Managing People through HR Strategies and Internal Marketing - Cioclov, Roxana; Cioclov (Petcu), Alexandra (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The following paper aims at presenting key concepts in regard to the interconnectivity between two similar and frequently confused practices – Human Resource Management and Internal Marketing. Therefore, it is intend to present both fields distinctively, in order to emphasise in the end the added value of the two working together. Given the fact that, in the specialised literature, there are different approaches on this subject and many questions raised regarding the separation of the instruments and particular objectives of the two practices, the paper presents a simplified approach on the HRM Cycle in comparison with the IM Cycle. Therefore, the paper is structured as follows: (1) HRM’s impact on the general activity of an organization – whether it is a manufacturing company or a service provider; (2) IM’s impact on the internal and external environment of the organization; (3) Analysis on the connection and in-/inter-/dependency of the two concepts and their meaning. Although HRM seems to bring numerous advantages to the organization, the current paper states that HR cannot be done at the same efficiency level in the absence of good Internal Marketing practices that allow the word-of-mouth to spread between the present and possible future employees. It is about a good branding that has to exceed the company’s geographical boundaries and to create the need, not only in terms of product consumer’s behaviour, but also in regard to employees that want to be part of the brand.